Elsa Morante's politics of writing : rethinking subjectivity, history, and the power of art - Lucamante, Stefania (Fairleigh Dickinson University Press, 2015)
This book revisits the philosophy and aesthetic Elsa Morante outlined in her literary writings, essays, articles, reviews, and poetry. Stefania Lucamante presents a fresh outlook at Morante's work to determine the importance of her work today, to appreciate her theoretical and stylistic legacy, and to understand why and which elements of her work have inspired Italian artists.